Manajemen Program Juz Amma untuk Meningkatkan Kemampuan Membaca Al-Qur’an Siswa SD Negeri 1 Serayukaranganyar Purbalingga - Sulung Aji Pangestu; Muh. Hanif (Jurnal Dirosah Islamiyah, 2024)
This research aims to determine the management of the juz amma program to improve students' Al-Qur'an reading skills at the Serayukaranganyar 1 Public Elementary School, Purbalingga. In this research, the qualitative method used is a case study type. The data collection procedure was carried out using the observation method, namely observation, interviews, namely a collection method using oral questions and answers with sources, and the documentation method, namely searching for data regarding something related to the research. The research results obtained are: This research examines the effectiveness of the Juz Amma program at the Serayukaranganyar 1 State Elementary School in improving students' ability to read and memorize the Al-Qur'an. The research results showed that this program was successful in increasing students' fluency in reading the Al-Qur'an by adhering to the rules of tajwid and tartil. This program includes the activity of reading one verse in turn, listening and copying the teacher's reading in turns, as well as providing opportunities for students to ask questions. Program management includes systematic preparation, implementation and supervision, with the active role of school principals, teachers and parents. The evaluation program is carried out periodically through daily notes, mid-semester assessments and end-of-semester assessments, ensuring that students' memorization targets and quality are achieved. Supporting factors for the program include student enthusiasm and parental support, while inhibiting factors include student concerns about memorization targets and differences in student abilities. This program received a positive response from the community and parents, and succeeded in improving students' ability to read and memorize the Al-Qur'an.